Pathomechanisms of Autoimmune Based Testicular Inflammation - Lustig, Livia; Guazzone, Vanesa A.; Theas, María S.; Pleuger, Christiane; Jacobo, Patricia; Pérez, Cecilia V.; Meinhardt, Andreas; Fijak, Monika (Frontiers in Immunology, 2020)
Infection and inflammation of the male reproductive tract are relevant causes of infertility. Inflammatory damage occurs in the special immunosuppressive microenvironment of the testis, a hallmark termed testicular immune privilege, which allows tolerance to neo‐antigens from developing germ cells appearing at puberty, long after the establishment of systemic immune tolerance. Experimental autoimmune orchitis (EAO) is a well-established rodent model of chronic testicular inflammation and organ specific autoimmunity that offers a valuable in vivo tool to investigate the pathological and molecular mechanisms leading to the breakdown of the testicular immune privilege. The disease is characterized by the infiltration of the interstitium by immune cells (mainly macrophages, dendritic cells and T cells), formation of autoantibodies against testicular antigens, production of pro-inflammatory mediators such as NO, MCP1, TNFα, IL6 or activins and dysregulation of steroidogenesis with reduced levels of serum testosterone. EAO leads to sloughing of germ cells, atrophic seminiferous tubules and fibrotic remodelling, parameters all found similarly to changes in human biopsies from infertile patients with inflammatory infiltrates. Interestingly, testosterone supplementation during the course of EAO leads to expansion of the regulatory T cell population and inhibition of disease development. Knowledge of EAO pathogenesis aims to contribute to a better understanding of human testicular autoimmune disease as an essential prerequisite for improved diagnosis and treatment.